Identifying economically vulnerable groups as the economic crisis emerged - Whelan, Christopher T.; Maitre, Bertrand (Economic & Social Studies, 2010)
A frequent refrain during recent debates on welfare cuts and tax increases has related to the need to ?protect the vulnerable?. However, it is far from clear that a consensus exists on which individuals or groups are to be included under this heading with a consequent lack of clarity for the policy implications of pursuing this goal. In this paper, operating with a conception of social exclusion that incorporates notions of dynamics and multidimensionality, we make use of EUSILC 2008 data for Ireland to clarify the distinction between income poverty and economic vulnerability. We then proceed to consider the relationship between these outcomes and multiple deprivation, financial pressures and perceptions of recent and future economic prospects. Our analysis is then extended to compare patterns of risk for poverty and vulnerability in relation to key socio-economic groups. Finally, we will consider the relationship between poverty and vulnerability and the distribution of welfare dependence. Our analysis suggests that the vulnerable but non-poor group may need to be a key focus of policy attention in the future.
Policy paper presented at a symposium on ?The Crisis, Welfare State Retrenchment and Social Cohesion: Lessons from Social Science?
Keywords: Poverty; Economic vulnerability; Irish economic crisis; Income distribution